Chemiluminescent Reactions of Luminol and N-Octylluminol with a Hypochlorite in Non-ionic Surfactants - T. V. Yankova; P. V. Melnikov; N. A. Yashtulov; N. K. Zaitsev (Тонкие химические технологии)
The chemiluminescent reaction of luminol is widely used for analytical purposes. Surface-active components of biological membranes are often present in biochemical studies and in many real objects of analysis. Their influence on the chemiluminescent reaction of luminol has not been systematically studied. Therefore, it is necessary to investigate this chemiluminescent reaction in organized molecular systems - micellar, vesicular and other systems simulating biological membranes. Micellar medium may also provide an additional opportunity to control chemiluminescent reactions, primarily with the aim of increasing their efficiency. The kinetics of the chemiluminescent oxidation of luminol and its hydrophobic analogue N-octylluminol with a hypochlorite ion in aqueous solutions and micellar solutions of non-ionic surfactant Triton X-100 was studied in the present work. It was shown that the growth and fading of the luminol and N-octylluminol chemiluminescence is adequately described by a two-exponential dependence, and the effective rate of increase in the intensity of chemiluminescence is directly proportional to the concentration of the hypochlorite ion. The dependences of the rate of accumulation and consumption of the intermediate product on the presence and concentration of surfactants in the reaction mixture are determined. The results are discussed in terms of the effect of localization of the reagents and intermediate reaction products.